RESPONSABILIDADE SOCIAL E CIDADANIA EMPRESARIAL FACE À SEGURANÇA NO TRABALHO – FASE II - ENDRUWEIT, ANDREAS A. B.; SCHNEIDER, ANDRESA; SACKSER, GILBERTO; DUARTE, LUIZ C. D. S.; RIBEIRO, LUÍS F. M.; ECKHARDT, MOACIR (Salão do Conhecimento, 2013)
Resumo